2022
DOI: 10.1590/1518-8345.6296.3834
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against human papillomavirus in Brazilian schoolchildren: National Survey of School Health, 2019

Abstract: Objective: to analyze the prevalence of schoolchildren vaccinated against human papillomavirus (HPV) and the reasons related to non-vaccination. Method: cross-sectional study, with data from the 2019 National Survey of School Health. The sample consisted of 160,721 students aged 13 to 17 years. The prevalence and confidence intervals (95%CI) of vaccinated adolescents were estimated according to location, sex, and administrative dependence of the school. The differences between the strata were evaluated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…The authors even noticed a three higher vaccination coverage when compared to the rates registered by the public service in the previous year (when it was already carried out in health centers). The increase in coverage observed in the months the study was carried out indicates the success of school vaccination [20].…”
Section: Place Of Vaccinationmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors even noticed a three higher vaccination coverage when compared to the rates registered by the public service in the previous year (when it was already carried out in health centers). The increase in coverage observed in the months the study was carried out indicates the success of school vaccination [20].…”
Section: Place Of Vaccinationmentioning
confidence: 93%
“…However, there was a migration to health units, and later there was a significant drop in the coverage rate. Silva et al [20] demonstrated adequate coverage when proposing to vaccinate young people in schools. The authors even noticed a three higher vaccination coverage when compared to the rates registered by the public service in the previous year (when it was already carried out in health centers).…”
Section: Place Of Vaccinationmentioning
confidence: 99%
“…Nesse sentido, é importante lembrar que a assistência de enfermagem apresenta-se fundamental para o paciente portador de diabetes, desde a ação de orientação até o acompanhamento e o acolhimento ao paciente, promovendo ao mesmo, incentivo, educação à saúde para a aprendizagem da convivência com a doença (SILVA et al, 2022).…”
Section: Referênciasunclassified
“…A enfermagem atua no processo educativo que engloba reeducação alimentar, atividade física, tratamento medicamentoso e cuidados com o pé diabético e também como motivação no processo de interação social (SILVA et al, 2022).…”
Section: Cuidados De Enfermagem Ao Paciente Com Dm1unclassified
See 1 more Smart Citation